Saturdays at sea - George, Jessica Day, 1976- (Bloomsbury, 2017)
"After traveling to the seaside kingdom of Lilah's betrothed prince, Lulath, Celie and her companions are busy training griffins, enjoying wedding festivities, and finishing construction of a grand ship built from parts of the Castle. But on their maidenvoyage, the Ship steers them far off course into uncharted waters"--